ENDOVASCULAR TREATMENT OF THE PATENT DUCTUS ARTERIOSUS - A. N. Pakholkov; E. S. Suslov; K. A. Lashevich; A. N. Fedorchenko; V. A. Porhanov (Инновационная медицина Кубани)
Correction of the patent ductus arteriosus (PDA) takes an important place in management of congenital heart defects (CHD). Untreated PDA can lead to heart failure due to left ventricular myocardial hypertrophy (LVH), pulmonary hypertension, bacterial endocarditis, pulmonary infection, and rarely the development of ductal wall aneurysm, its calcification and further rupture.It is believed that the closure of PDA is indicated in any child or adult who develops pathognomonic symptoms: expansion of the left heart; the presence of signs of pulmonary hypertension with left-right blood discharge; prior endocarditis. In asymptomatic patients with PDA accompanied by left ventricular hypertrophy closure of the duct is indicated to reduce the risk of further complications.There were various surgical methods of PDA treatment discovered in the period of the development of medical industry. Previously the most common intervention was ligation of the duct, accompanied by thoracotomy. However, in the present days the ligation of PDA is extremely rare. Endovascular occlusion has taken the lead in the modern practice. Its purpose is to close the duct with intravascular access with help of specialised tools.In this article we present a case of PDA management in a patient with clinical manifestation of PDA at the age of 35 years.